MASTERY OF ARABIC VOCABULARY THROUGH THE ‘ILQO’ MUFRADAT’ ACTIVITY: A PHENOMENOLOGICAL STUDY OF THE EXPERIENCES OF FEMALE STUDENTS IN YEAR 7 AT THE MUHAMMADIYAH BOARDING SCHOOL (MBS) IN KERTEK, WONOSOBO - Tsalitsa Nurun Muntadziroh; Hidayatu Munawaroh; Nugroho Prasetya Adi (Jurnal Ikhtibar Nusantara, 2026)
This study aims to reveal the experiences of seventh-grade female students in mastering Arabic vocabulary through Ilqo' Mufradat activities at SMP Muhammadiyah Boarding School (MBS) Kertek Wonosobo. This study employed a qualitative approach with a phenomenological method. Data were collected through classroom observations, in-depth interviews with the school principal, the ustadzah who taught Ilqo' Mufradat to seventh-grade female students, and representatives of seventh-grade female students who participated in the Ilqo' Mufradat activities, and were supported by documentation. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results of the study indicate that Ilqo' Mufradat activities provide positive experiences for female students. These activities foster enjoyment, enthusiasm, increased learning motivation, and improved Arabic vocabulary mastery. However, the students also encountered obstacles during the activities, particularly difficulties in memorizing and understanding the meanings of the vocabulary. To address these challenges, the ustadzah implemented several strategies, including a weekly murajaah program, reward-based reinforcement, and the use of a pocket dictionary for students.